Comparison of Effectiveness of Nebulized N-Acetylcysteine Solution (Mucolytic Therapy), Nebulized Salbutamol and Nebulized Ipratropium Bromide In Treatment of Children with Acute Bronchiolitis - Saleem Ahmed Khoso, Jalaluddin Akber, Syed Zafar Mehdi, Arshad Hamid Khan, Saba Sohrab, Tahira Saeed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Bronchiolitis is a viral mediated disease that results in acute inflammation in the lower respiratory tract. It occurs in infants and children under 2 years of age. The vast majority of infants’ experience at least 01 episode of bronchiolitis and 2-3% of all infants can be hospitalized for bronchiolitis in the 1st year. With an increasing rate having risen by an average of 1.8% annually in European country and a small percentage even need critical care. Children who are hospitalized for bronchiolitis currently only receive fluid replacement, additional oxygen and respiratory support. Bronchiolitis is most common motivator for hospital admissions in many nations. Respiratory syncytial virus (RSV) is most common virus causes bronchiolitis, and also causes infections during the winter months. Objective: To determine the comparison of effectiveness of nebulized N-acetylcysteine solution (mucolytic therapy), nebulized salbutamol and nebulized ipratropium bromide in treatment of children with acute bronchiolitis at a tertiary care hospital. Materials & Methods: All patients who fulfilled the inclusion criteria and visited to Baqai Medical University Hospital, Karachi from April 17, 2019 to October 16, 2019 were included in this Prospective Randomized Control Trial (lottery method). Informed consent was taken after explaining the procedure, risks and advantages of the study. Children from either gender having provisional diagnosis of acute bronchiolitis between 2 to 24 months of age were included and divided in three groups in our study. Each group obtained three treatments every day, introduced at intervals of eight hours for three days. Patients had been tested on admission, at 8 hours and every morning for severity of disease. For assessing improvement, scientific severity score turned into used to peer the effectiveness of nebulized N-acetylcysteine solution (mucolytic therapy), nebulized salbutamol and nebulized ipratropium bromide in bronchiolitis. All the collected data were entered into the proforma attached at the end and used electronically for research purpose. Results: 81 study cases of these, 44 (54.3%) were males while 37 (45.7%) were females. Our study cases mean age in Nebulized N-acetylcysteine was 9.4±6.3, in Nebulized Salbutamol and Ipratropium Bromide was 10.8±6.7 and 12.0±6.6 months, respectively. In group wise comparison of clinical severity score at baseline, 8, 24 and 72 hours, highly significant difference was found among the group at baseline, 8, 24 and 72 hours i.e., P ≤ (0.05) within the groups while on the other hand non-significant difference i.e., (0.633) was showed between the group at baseline among nebulized N-acetylcysteine, nebulized salbutamol and ipratropium bromide group respectively. Conclusion: In the lights of our findings, it is to be concluded that nebulized salbutamol was more effective in improvement of clinical severity score with shorter duration of hospital stay. Furthermore, it is to be concluded that there is a need to have further studies with larger sample size in different centers in Pakistan to validate the findings of current study. Keywords: N-acetylcysteine Solution, Nebulized Salbutamol, Nebulized Ipratropium Bromide, Acute Bronchiolitis